Clinical study of various modalities of treatment for fistula in ano at a tertiary care hospital - Tated, Sushrut Pradeep; Sharma, Kuldeep; Hatkar, Ashish Ashokrao (International Surgery Journal, 2017)
Background: Despite the ease of diagnosis, establishing a cure is problematic as many patients tend to let their disease nag them rather than treatment. Also, due to site of this disease many patients delay the treatment. Objectives was to study the various etiologies of fistula in ano, to study the different modes of clinical presentations of these fistulae-in-ano, efficacy of different modalities of surgical approach with reference to recurrence of fistulae. Methods: Hospital based cross sectional descriptive study was carried out among 81 eligible patients of fistula in ano. Local Examination, Per Rectal Examination, Proctoscopy was done to assess the external opening, internal opening and fistula tract. Patients were advised Fistulogram and sent to Department of radiology on outpatient basis for the same. Patients with fistulography report were admitted and surgical treatment was planned according to the fistulography report. Appropriate surgery was planned. Specimens were sent to histopathology. Results: Commonest age of presentation was between 30-40 years. Males were more commonly affected. Swelling in perineal region was commonest mode of presentation. Fistula with only one opening was around 85.18%. Anteriorly situated fistula was around 14.81%. Low level fistula was more common. Majority of patients i.e. 74.07% underwent fistulectomy. 9.87% patients underwent fistulotomy. 16.04% patients underwent setonthresd placement. Three Patients developed recurrence. Conclusions: Fistulotomy is associated with slightly high recurrence but low chances of anal incontinence as compared to fistulectomy.